CYTOTOXIC SATURATED FATTY ACIDS FROM THE INDONESIAN SEA CUCUMBER Holothuria sp. - Hedi Indra Januar; Muhammad Nursid; Ekowati Chasanah (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2014)
Sea cucumbers are one of Indonesia’s marine organism with the potential to be developed as possible herbal medicines. In a preliminary study of cytotoxic activity of ethanol extracts of 14Indonesian sea cucumber species, the most active extract came from the Holothuria sp. Thecurrent research aimed to identify the major cytotoxic component in the sea cucumber Holothuriasp., that yielded the most active extract. The samples were collected from South Lampung beach.Isolation of the cytotoxic component was done employing liquid flash and preparative reversedphase (C 18) chromatography. Cytotoxic ity evalu atio n of fractio ns collected durin g thechromatography was conducted using the MCF-7 tumor cell line. Elucidation of the structure ofmost active isolate was done by NMR (Nuclear Magnetic Resonance) spectroscopy and GC-FID(Gas-Chromatography-Flame Ionisation Detector) analysis. The results of these analyses showedthe most active compound to be stearic acid; IC 50towards MCF-7 cells 10.32 ppm.